MULTISCALE GIS-BIM METHODOLOGICAL APPROACHES AND DIGITAL SYSTEMS FOR THE KNOWLEDGE OF THE MODERN ARCHITECTURAL HERITAGE IN ITALY. THE RURAL VILLAGE “LA MARTELLA” IN MATERA - Pontrandolfi, R. (International archives of the photogrammetry, remote sensing and spatial information sciences., 2020)
The use of digital tools and approaches related to the ICT field is now of particular importance for the knowledge and enhancement of the modern architectural heritage. The contribution intends to focus on the theme of cognitive analysis and digital documentation of some examples of public residential buildings of historical and testimonial value of the period following the second World War, in Italy, in order to define appropriate recovery strategies. Unlike buildings of historical-monumental importance, which have been the subject of studies and surveys involving the use of digital tools for several years now, little interest is still attributed to the knowledge of the building heritage of the second half of the Twentieth Century to which historical value is attributed. The interventions in the 1950s by INA Casa and U.N.R.R.A. Casas, in Italy, constitute interesting case studies that are worthy of further research and cognitive analysis based on holistic and multi-scalar approaches. In this context, the surveys and research in progress on the historical buildings of the rural village “La Martella” in Matera (1951–55) are an interesting example of experimentation using GIS-BIM digital platforms for the implementation of a multiscale knowledge methodology (from the territorial scale, to urban blocks to individual buildings) that provides for the structuring and implementation of an integrated information database (Common Data Environment) aimed at defining recovery strategies for the protection and enhancement of the historical buildings of the village, through the concept of interoperability for the systematization of archive sources and data obtained through surveys on the existing situation.